Manajemen Pembelajaran Kelas Digital Berbasis Google Workspace for Education - Hafid, Hafid; Barnoto, Barnoto; Shonhadji; Abuhsin, Jupri (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2022)
This study aimed to determine the digital classroom learning management in SMP Negeri 1 Kedungpring. The research methodology in this article uses qualitative research with a case study approach. The data sources are informants, events, locations, and documents. Then check the validity of the data using credibility, dependability, transferability, and confirmability. The results of this study are 1) planning for digital classroom learning based on google workspace for education consists of planning, organizing, implementing, monitoring, and evaluating. 2) implementation of digital classroom learning based on Google workspace for education consists of creating an account with a school domain, activating an account, creating virtual classes, and carrying out digital classroom learning. Using the features of google classroom, google docs, google Sheets, Google Slides, google jaw board and google sites. 3). Evaluation of digital classroom learning based on Google Workspace for Education using a google form with a report that will be automatically sent to the email of the Principal, Head of Curriculum, and Subject Teachers.